2019
DOI: 10.5114/pjp.2019.93135
|View full text |Cite
|
Sign up to set email alerts
|

Acquired von Willebrand syndrome associated with plasma cell myeloma – a rare histopathological bone marrow image

Abstract: Acquired von Willebrand syndrome (AVWS) is a rare bleeding disorder that is associated with a variety of underlying diseases. We report a case of AVWS associated with plasma cell myeloma. The patient was a 57-year-old male with recurrent bleeding symptoms for a few months. Physical examination was normal. Laboratory studies revealed isolated prolongation of the activated partial thromboplastin time. His factor VIII activity, von Willebrand factor (VWF) Ag, and VWF activity were low. Bone marrow aspirate showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In addition to the inherited form, several other forms of the disease have been reported, including autoantibodies against VWF and conditions that may cause rapid degradation and clearance of VWF and adsorption of VWF on malignant cells. This kind of disease is called acquired von Willebrand syndrome (AVWS) [ 12 ]. Studies have also reported that alloimmunization in patients of type III vWD may also lead to clearance of VWF .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the inherited form, several other forms of the disease have been reported, including autoantibodies against VWF and conditions that may cause rapid degradation and clearance of VWF and adsorption of VWF on malignant cells. This kind of disease is called acquired von Willebrand syndrome (AVWS) [ 12 ]. Studies have also reported that alloimmunization in patients of type III vWD may also lead to clearance of VWF .…”
Section: Introductionmentioning
confidence: 99%